Relações comunitárias e aspectos psicossociais da imigração haitiana no Rio Grande do Sul - Weber, João Luís Almeida (2017)
The present thesis aimed to explore the phenomenon of haitian immigration in Rio Grande do Sul, regarding acculturation orientations, and how these could be related to sociodemographic factors, prejudice and quality of life. For that, two empirical studies were carried out, with a cross-sectional quantitative design. The theoretical model used was the Acculturation Interactive Model, which approaches the theme both from the perspective of the immigrants, in this case the haitian immigrants, and how it approaches from the host population, which in this research was carried out in a city in the countryside of the state of Rio Grande do Sul, where the largest number of immigrants resides in proportion to the local population. The first study, entitled "Haitian Immigration: Psychosocial Aspects and Acculturation Orientations", was composed by 67 Haitian immigrants who immigrated between 2010 and 2016. The results showed that this group of immigrants is predominantly composed of men, with high schooling and speakers of the Portuguese language. The most frequent acculturative orientation integration, which is more present among men; between those who accessed the social assistance system; among the youngest; the ones with more fluency in other languages, and the ones that have arrived in Brazil longer. In addition, perceived prejudice and quality of life were better compared to studies with the same population in other countries. The second study, entitled "Acculturative Orientations and Ethnic-Racial Prejudice toward Haitian Immigrants in Brazil," similarly explored the same issues - acculturation orientations, prejudice and quality of life - in a Brazilian host community. The results showed that this community also adopts, in its majority, acculturation orientations of integration towards the immigrants. The predictive factors for the acculturative orientations were also identified. It was noticed that orientations, identified as most beneficial to the migratory process, such as integration, individualism and transformation, have as predictive factors a lower score on racism and higher on quality of life. On the other hand, it was observed that the acculturation orientations that are less welcoming towards immigrants, in the case - assimilation, exclusion and segregation – have as associated factors a greater racial prejudice and a lower perceived quality of life. Also, it has been identified that racial prejudice, in its dimension of denial of prejudice, is greater among men, who are also more likely to adopt the acculturative orientation of segregation. The notes of the two studies reveal that both communities share the predominance of the acculturative orientation of integration. By consensually adopting this orientation, it is expected a potentially more harmonious relationship between the two collectives. The development of integration favors attitudes of diversity, equity and the reduction of prejudice and conflict. Finally, the findings of this research offer a panorama, although circumscribed and delimited of this reality, but that can serve as a support to think public policies and interventions that aim both to raise the awareness of the brazilian population as to this emerging theme, as to present reception possibilities and the promotion of human rights for immigrant and refugee groups in Brazil.